Editing Some Couplets of Manūchihrī Dāmghānī's Divan - Mahmoud Rahimi; Naser Rahimi; Mahmoud Abedi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Despite having been published several times, no satisfying edition of Manūchihrī Dāmghānī's Divan has been produced, and the need for a critical edition of the text is in order. Further attempts and more precise examinations are required to improve the text. This article aims to assess certain lines by Manūchihrī, challenging the accuracy of the chosen variants from the viewpoint of textual criticism. Furthermore, the authenticity of some lines ascribed to the poet will be examined considering textual evidence. In the process of this assessment, some new alternative variants will be recommended. In order to support the recommended variants, textual evidence will be adduced by utilizing the earliest surviving manuscripts of Manūchihrī’s poems and taking advantage of a number of old sources.